2016
DOI: 10.1016/j.cortex.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of anterior temporal regions critical for retrieving names of unique and non-unique entities reflects underlying long-range connectivity

Abstract: Lesion-deficit studies support the hypothesis that the left anterior temporal lobe (ATL) plays a critical role in retrieving names of concrete entities. They further suggest that different regions of the left ATL process different conceptual categories. Here we test the specificity of these relationships and whether the anatomical segregation is related to the underlying organization of white matter connections. We reanalyzed data from a previous lesion study of naming and recognition across five categories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 124 publications
(179 reference statements)
4
48
4
Order By: Relevance
“…A. Wilson et al, 2012; Woollams et al, 2007). This conforms with a recent proposal that the left lateral temporal neocortex plays an intermediary role in mapping between ventrally-situated transmodal conceptual knowledge representation and the frontal speech production network, subtending lexico-semantic processes such as reading and naming (Hoffman et al, 2015; Mehta et al, in press). However, the present study highlights a mid portion of the middle temporal gyrus that is considerably more posterior than the typical area of atrophy observed in svPPA and the region implicated in prior imaging studies of reading.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A. Wilson et al, 2012; Woollams et al, 2007). This conforms with a recent proposal that the left lateral temporal neocortex plays an intermediary role in mapping between ventrally-situated transmodal conceptual knowledge representation and the frontal speech production network, subtending lexico-semantic processes such as reading and naming (Hoffman et al, 2015; Mehta et al, in press). However, the present study highlights a mid portion of the middle temporal gyrus that is considerably more posterior than the typical area of atrophy observed in svPPA and the region implicated in prior imaging studies of reading.…”
Section: Discussionsupporting
confidence: 92%
“…It is increasingly apparent that there are differences not only between the left and right temporal lobe but also within each rostral temporal lobe in terms of cytoarchitectonics, connectivity (Binney et al, 2012; Ding, Van Hoesen, Cassell, & Poremba, 2009; Pascual et al, 2015) and functional activation during tasks (Rice, Lambon Ralph, et al, 2015) which further implies intra-hemispheric relative functional specialization of rostral temporal sub-divisions (Binney et al, 2012; Mehta et al, in press; Visser, Jefferies, Embleton, & Lambon Ralph, 2012). For example, within the left rostral temporal lobe, the left basal region (anterior fusiform gyrus) is equally activated by nonverbal and verbal semantic tasks and thus appears to play a role that is transmodal in nature (Shimotake et al, 2014; Visser & Lambon Ralph, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, in that study, we found no other region in left anterior lateral or temporopolar cortex that tracked perceived lifetime Running Head: Medial Temporal Lobes and Familiarity Impairments 21 familiarity. The latter result is important because left anterior lateral and temporopolar cortex have been implicated in conceptual processing in other semantic task contexts (see Mehta et al, 2016;Rice et al, 2015, for review), and these structures were also resected in NB. Although the findings of the present study do not allow us to rule out that the behavioural abnormalities we observed are due to the inclusion of left anterior lateral or temporopolar cortex in NB's lesion, findings from our previous fMRI study argue against this interpretation.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies of individuals with semantic dementia or aphasia have implicated the UF in semantic retrieval (Han et al, 2013; Harvey et al, 2013), while other studies suggest the UF plays no role in semantic retrieval (Duffau et al, 2009) or only plays a role in retrieving proper names and unique entities (Mehta et al, 2016; Papagno et al, 2014). Studies reporting that UF microstructure is correlated with semantic cognition have also implicated the IFOF (De Zubicaray et al, 2011) which is geographically proximal to the UF at some points, making it difficult to ascertain whether the UF itself plays an essential role in semantic processing.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, terminations of the ILF in the posterior temporal lobe converge with these findings. Moreover, a recent study of naming and recognition of concrete entities in patients with brain lesions, found the ILF to be associated with naming impairments for non-unique entities (Mehta et al, 2016). Visual objects form the foundation of concrete semantic knowledge and ILF microstructure has been shown to relate to object processing (Ortibus et al, 2012; Shinoura et al, 2007).…”
Section: Discussionmentioning
confidence: 99%